2016
DOI: 10.1177/0363546516644718
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects of Leukocyte-Rich Platelet-Rich Plasma on Rabbit Tendon Stem Cells In Vitro

Abstract: This study revealed the direct effects of different compositions of PRP on TSCs and provided basic scientific data to help understand the cellular and molecular mechanisms of the efficacy of PRP treatment in clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…This is important, because leukocyte-rich PRP is detrimental to the proliferation of some stem/progenitor cells, leading to impaired tissue healing, because leukocytes inhibit the release of growth factors, such as VEGF, EGF, TGFβ 1 , and PDGF, increasing catabolic cytokine concentrations and causing inflammation and apoptosis. 47 50 Therefore, differences in PRP composition due to different PRP-separation devices or physiological changes in the patient may account for some of the variability in the efficacy of PRP on pain reduction. 51 , 52 …”
Section: Introductionmentioning
confidence: 99%
“…This is important, because leukocyte-rich PRP is detrimental to the proliferation of some stem/progenitor cells, leading to impaired tissue healing, because leukocytes inhibit the release of growth factors, such as VEGF, EGF, TGFβ 1 , and PDGF, increasing catabolic cytokine concentrations and causing inflammation and apoptosis. 47 50 Therefore, differences in PRP composition due to different PRP-separation devices or physiological changes in the patient may account for some of the variability in the efficacy of PRP on pain reduction. 51 , 52 …”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates enhanced COL1A1, COL3A1, decorin, fibronectin, aggrecan and connective tissue growth factor (CTGF) expression and reduced MMP-1 expression after exposure to LP-PRP. Similarly, the recent in vitro study by Zhang (Zhang et al 2016 ) showed that the exposure of rabbit tendon stem cells to LR-PRP decreased expression of VEGF, epidermal growth factor (EGF), Transforming Growth Factor Beta − 1 (TGF-β1) and platelet-derived growth factor (PDGF). Moreover, it reduced the production of collagen when compared to LP-PRP.…”
Section: Treatment Optionsmentioning
confidence: 85%
“…Moreover, the release of pro-inflammatory factors (cytokine and metalloproteinase) by the leukocytes may lead to deterioration of the extracellular matrix. Zhang et al [85] published the hypothesis that PRP containing high levels of leukocytes (L-PRP) increases the concentration of catabolic cytokine and induces inflammation and apoptosis of tendon cells. This study compared the effects of L-PRP and PRP on the morphology, proliferation, and differentiation of tendon cells.…”
Section: The Impact Of the Concentration Of Red And While Blood Cellsmentioning
confidence: 99%